The relationship between temporary team emotional intelligence and team performance of high-level basketball referees: the chain mediating role of swift trust and shared mental models - Wang, Y.; Wang, Z.; Tian, Y.; Chen, Z.; Yang, S. (International Journal of Sport and Exercise Psychology, 2026)
This study explores the relationship between team emotional intelligence and team performance among Chinese basketball referees` temporary teams through the mediating roles of swift trust and shared mental models. This study surveyed 198 high-level referees in China. Bias tests, descriptive statistics, and mean difference tests were utilised to analyze the data, while regression analysis combined with PROCESS v4.1 was employed to test the mediating effects. Findings revealed that team emotional intelligence (r = 0.489, p < 0.01), swift trust (r = 0.623, p < 0.01), and shared mental models (r = 0.712, p < 0.01) each showed positive correlations with team performance. Team emotional intelligence was not a significant direct predictor of team performance (ß = 0.104, p > 0.05); however, it was indirectly related to team performance through three paths: the partial mediating effect of swift trust (ß = 0.170, 95% CI: 0.048, 0.307), the partial mediating effect of the shared mental models (ß = 0.135, 95% CI: 0.06, 0.223), and the complete chain-mediating effect of swift trust and shared mental models (ß = 0.247, 95% CI: 0.159, 0.354). These results suggest that team emotional intelligence is associated with team performance through both mediators and their sequential interplay.